Persepsi Wartawan di Sumatera Selatan Terhadap Praktik Jurnalisme Warga pada Akun Instagram @PlgLipp - Yosse Sartika Putri; Choiriyah, Choiriyah; Ahmad Harun Yahya (Social Science and Contemporary Issues Journal, 2024)
Journalists are aware of and frequently access information from the Instagram account @plglipp. They also believe that citizen journalism on this account is very helpful, engaging, and provides timely updates. Journalists hope that in the future, the @plglipp admins will present information clearly and accurately. Citizen journalism on the @plglipp account has its strengths and weaknesses. Its strengths lie in its effective and timely delivery of information, while its weaknesses include providing incomplete information and a lack of full coverage.